Perceptions Of Indonesian University Of Education Academics On Corruption And Integrity Of Citizenship - Alya Zahra Rahma Putri; Aurevia Videlya Devanata; Fathimah Zahrah Lazmi; Salwa Rasyidah Muthmaina; Syawaliah; Dadi Mulyadi Nugraha (PT. Gudang Pustaka Cendekia, 2025)
This study observes university students' perspectives on corruption and civic integrity in Indonesia through a survey of 24 active students. The survey covered aspects such as awareness of corruption, the importance of personal integrity, and the role of students in combating corruption. The majority of respondents acknowledge the importance of integrity in daily life, demonstrate a fair understanding of corruption issues, and recognize a significant role for students in anti-corruption efforts. However, skepticism exists regarding the effectiveness of Indonesia's legal system in addressing corruption. The findings underscore the need for enhanced education on the dangers of corruption, the reinforcement of integrity values, and a call for more transparent and rigorous law enforcement.